Co-option of Hair Follicle Keratins into Amelogenesis Is Associated with the Evolution of Prismatic Enamel: A Hypothesis - Beniash, Elia (Frontiers in Physiology, 2017)
Recent discovery of hair follicle keratin 75 (KRT75) in enamel raises questions about the function of this protein in enamel and the mechanisms of its secretion. It is also not clear how this protein with a very specific and narrow expression pattern, limited to the inner root sheath of the hair follicle, became associated with enamel. We propose a hypothesis that KRT75 was co-opted by ameloblasts during the evolution of Tomes’ process and the prismatic enamel in synapsids.